Pengaruh Ego Depletion dan Beban Kerja terhadap Audit Judgment Quality: Studi Empiris pada Auditor BPK RI Perwakilan Sumatera Barat - Mellynia Tri anita Rahim; Eka Fauzihardani (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to examine the effect of ego depletion and workload on audit judgment quality. This type of research data uses primary data. Primary data is obtained from questionnaires that have been filled out by respondents. The sample used in this study were 44 respondents of the BPK RI auditors from West Sumatra Representatives. Statistical data analysis techniques performed in this study is multiple regression analysis. The results of this study indicate that ego depletion and workload have no effect on audit judgment quality.